The Impact of Profitability, Dividend, and Firm Size on Stock Prices in the Consumer Goods Sector on the Indonesia Stock Exchange for the Years 2022-2024: The Effects of Global Geopolitical Uncertainty - Shafana, Nurul Fikri Rahmah; Bararisty, Zico; Yulianto, Agung (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to analyze the effect of corporate profits, Dividend, and Firm Size on stock prices in consumer goods companies listed on the Indonesia Stock Exchange. The data used are secondary data in the form of company financial reports, covering a five-year observation period and 295 observations. The analytical method used in this study is multiple linear regression analysis with the assistance of statistical software. The results show that corporate profits and Firm Size have a positive and significant effect on stock prices, indicating that financial performance and company scale are the main factors investors consider when making investment decisions. Meanwhile, Dividend have no significant effect on stock prices, indicating that investors are more oriented towards potential capital gains than dividend income. This study is expected to contribute to investors, company management, and future researchers in understanding the factors that influence stock prices.